2009
DOI: 10.1111/j.1365-2591.2009.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial pulpotomy on caries‐free teeth using enamel matrix derivative or calcium hydroxide: a randomized controlled trial

Abstract: After 6 months, healthy pulps capped with Ca(OH)(2) had more favourable results than counterparts capped with EMDgel. However, similar clinical and radiographic results were seen in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 21 publications
1
31
2
4
Order By: Relevance
“…Kiatwateeratana ve arkadaşlarının 38 yaptıkları çalış-mada küçük azı dişe parsiyel pulpotomi uygulanarak EMD ve kalsiyum hidroksit ile tedavileri yapılarak histolojik, radyografik ve postoperatif olarak karşılaştırmala-rı yapılmıştır. İlk 2 hafta EMD ile tedavi edilen dişlerde belirgin bir şekilde daha az hipersensitivite görülmüştür.…”
Section: Tüm Hakları Saklıdır © 2014 Gazi üNiversitesiunclassified
“…Kiatwateeratana ve arkadaşlarının 38 yaptıkları çalış-mada küçük azı dişe parsiyel pulpotomi uygulanarak EMD ve kalsiyum hidroksit ile tedavileri yapılarak histolojik, radyografik ve postoperatif olarak karşılaştırmala-rı yapılmıştır. İlk 2 hafta EMD ile tedavi edilen dişlerde belirgin bir şekilde daha az hipersensitivite görülmüştür.…”
Section: Tüm Hakları Saklıdır © 2014 Gazi üNiversitesiunclassified
“…Clinical trials have shown that partially pulpotomized EMD gel-treated teeth had significantly less tooth hypersensitivity compared to Ca(OH) 2 -treated [12] with a positive effect on wound healing/new tissue and hard tissue formation [13]. …”
Section: Introductionmentioning
confidence: 99%
“…These cells join together to form a network [7]. All pulp vessels have very thin walls due to muscularis mucosa reduction.…”
Section: Core Pulp -Cell-rich Zonementioning
confidence: 99%
“…Attempts are also made to cover wounded and open pulp with bonding systems [14,18], glass ionomer cement [8] or enamel matrix proteins [7]. The effects are debatable, cause inflammation, including necrosis, and no dentin bridge has been found [12,15,16].…”
Section: Age-related Changes In Endodontiummentioning
confidence: 99%
See 1 more Smart Citation